2021
DOI: 10.3389/fcvm.2021.638679
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Lipoprotein(a) With Coronary Atherosclerotic Burden and All-Cause Mortality in Patients With ST-Segment Elevation Myocardial Infarction Treated With Primary Percutaneous Coronary Intervention

Abstract: Background: The coronary atherosclerotic burden in patients with ST-segment elevation myocardial infarction (STEMI) has been identified as the main predictor of prognosis. However, the association of lipoprotein(a) [Lp(a)], a well-established proatherogenic factor, with atherosclerotic burden in patients with STEMI is unclear.Methods: In total, 1,359 patients who underwent percutaneous coronary intervention (PCI) for STEMI were included in analyses. Three prespecified models with adjustment for demographic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Over the last 10 years, genetic and epidemiologic evidence supported that high Lp(a) level was a risk factor for cardiovascular disease [ 3 6 ]. Moreover, previous studies, including the present authors, revealed that Lp(a) was positively associated with recurrent cardiovascular events in patients with acute coronary syndrome (ACS) who underwent percutaneous coronary intervention (PCI) [ 7 10 ]. However, there are no approved pharmacologic therapies that are specifically aimed at lowering Lp(a) levels.…”
Section: Introductionmentioning
confidence: 77%
“…Over the last 10 years, genetic and epidemiologic evidence supported that high Lp(a) level was a risk factor for cardiovascular disease [ 3 6 ]. Moreover, previous studies, including the present authors, revealed that Lp(a) was positively associated with recurrent cardiovascular events in patients with acute coronary syndrome (ACS) who underwent percutaneous coronary intervention (PCI) [ 7 10 ]. However, there are no approved pharmacologic therapies that are specifically aimed at lowering Lp(a) levels.…”
Section: Introductionmentioning
confidence: 77%
“…Ultimately, 18 full-text articles, encompassing a total of 18,168 patients (13,843 male, 4,325 female), were selected for the comprehensive pooled analysis ( 20 23 , 25 28 , 33 42 ). Of these articles, 5 were prospective cohort studies ( 21 , 23 , 34 , 35 , 40 ), 10 were retrospective cohort studies ( 20 , 22 , 25 , 26 , 28 , 33 , 36 39 ), and 3 were observational cohorts ( 4 , 27 , 41 ). The encompassed investigations in this analysis spanned the period from 2009 to 2023.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies ( 22 , 23 , 25 , 27 , 33 , 34 , 40 ) were included in the analysis to investigate the relationship between elevated Lp (a) levels and the risk of all-cause mortality ( Figure 3A ). Utilizing a random-effects model, the pooled Hazard Ratio (HR) for all-cause mortality was 1.36 (95% CI: 1.05–1.76) when comparing high to low category of Lp (a) levels.…”
Section: Resultsmentioning
confidence: 99%
“…33 A prospective study comprising 1359 patients who were submitted to percutaneous coronary intervention (PCI) for STEMI showed that patients in the upper tertile of Lp(a) concentrations had a high occurrence of HF during hospitalization. 34 Also, patients with high concentrations of Lp(a) (>19.1 mg/dL) had higher risks for a greater Gensini score ( P for trend = 0.03) of CAD severity, and no reflow ( P for trend = 0.002) after adjusting for demographic features and risk factors. Over a median of 2.5 years, 132 deaths (9.95%) were recorded.…”
Section: Clinical Studiesmentioning
confidence: 90%